Estudo da fotoluminescência do óxido de zinco na forma de pó, filme e pastilha - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Materials of technological interest are being increasingly targeted, mainly by its use in optoelectronic devices. One of these materials is zinc oxide (ZnO) due to the direct band gap around 3.3 eV and its excitation energy of 60 meV at room temperature. In the present study, three different types of ZnO sample were prepared in the powder, bulk and film shapes. The influence of the pressure-assisted thermal treatment on the different test specimens was evaluated. All the samples were synthesized using the Pechini method and, for the film samples, was used the spin coating technique of for film deposition. Through the TG / DTA analysis it was determined that the ideal temperature for sintering of the materials. By the technique of X-ray diffraction it was possible to observe the presence of ZnO phase. The fieldscanning electron microscopy technique (SEM-FEG) allowed the visualization of the morphologies of the samples, which were presented in nanometric scale in the powder and film forms and in the micrometric scale for the bulk. The pressure treatment caused changes in the morphology in the bulk and film samples. The Raman spectroscopy technique was used to evaluate the chemical composition of the samples, it was possible to check that the pressure increases the crystallinity of the materials. The optical properties were studied by the spectroscopy technique in the UV-visible region and by photoluminescence (PL) spectroscopy. The band gap of the samples was calculated by the Kubelka-Munk method using UV-vis, where differences in the samples with and without the pressure treatment were related. By the technique of PL, the samples of powder and bulk presented two characteristic peaks, one less intense in the region of the ultraviolet and another in the visible region; however in the film samples were detected a third peak in the visible region. For all samples, it was found that the pressure treatment caused an increase of intensity and an enlargement in the peaks.
Keywords: Fotoluminescência; tratamento térmico assistido por pressão; propriedades óticas; Photoluminescence; pressure assisted treatment; optical properties; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA